Student Motivation to Follow the Student Creativity Program - Ismail, *Ismail; Putri, Ridiya Samita; Zulfadhli, Zulfadhli; Mustofa, Achmad; Musfiana, Musfiana; Hadiyani, Rahmilia (Universitas Syiah Kuala, 2022)
This study aims to determine (1) the factors that cause USK FKIP students to be less motivated to participate in PKM and (2) how to increase the motivation of USK FKIP students to participate in PKM. This article uses a qualitative approach with a descriptive type of research. The sampling technique used was quota sampling and data collection techniques in the form of observation, interviews, documentation and data triangulation. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The findings in this study could be presented as follows: The factors causing students to be less motivated to participate in PKM activities are (1) an intrinsic factors (intelligence 25%, attention 19%, interest 14%, motive 12%, maturity 13% and fatigue 17%), (2) the extrinsic factors (class schedules 20%, curriculum 24%, relations between students and students 28%, relations between students and lecturers 28%). Efforts made to increase students motivation to participate in PKM activities are: (1) efforts made by the Vice Dean for student affairs, which consist of intrinsic factors (attention 37.5% and motivation 62.5%) and 100% factors of extrinsic is student-teacher relationship factor (2) efforts made by the study program are intrinsic factors consisting of 22% attention, 37% motivation and 41% readiness and extrinsic factors consist of 27% curriculum and 73% relationship between lecturers and students. The effort expected by students consists of intrinsic factors (intelligence 34% and attention 66%), while extrinsic factors (curriculum 16%, relationships between students and students 40% and relationships between lecturers and students 44%).